2007
DOI: 10.1007/s11427-007-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and developmental expression of the gene encoding the prothoracicotropic hormone in the beet armyworm, Spodoptera exigua

Abstract: Prothoracicotropic hormone (PTTH), a neuropeptide hormone stimulating the prothoracic glands to synthesize ecdysone, plays an important role in regulating postembryonic development in insects. The cDNA encoding PTTH was isolated and sequenced from the beet armyworm, Spodoptera exigua (Spe). The deduced amino acid sequence is composed of a signal peptide, a peptide (65 amino acids) of unknown function, and a mature PTTH molecule (111 amino acids). The Spe-PTTH shows similarities (45.5%-70.3%) to other known PTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…These peaks were clearly reduced in the newly-molted 2 nd and 3 rd instar larvae. This expression pattern is similar to those reported in other insects 23 34 38 39 40 . In addition, it has been reported that the expression pattern of a gene which has an inerratic change around ecdysis, is almost synchronized with that ecdysone titer in insects 41 .…”
Section: Discussionsupporting
confidence: 89%
“…These peaks were clearly reduced in the newly-molted 2 nd and 3 rd instar larvae. This expression pattern is similar to those reported in other insects 23 34 38 39 40 . In addition, it has been reported that the expression pattern of a gene which has an inerratic change around ecdysis, is almost synchronized with that ecdysone titer in insects 41 .…”
Section: Discussionsupporting
confidence: 89%
“…Sequence alignment indicates a huge variation in PTTH at the primary structure level, suggesting that the PTTH molecule evolved rapidly from a common ancestral gene. Following the first report on the cDNA structure of PTTH in B. mori (Kawakami et al ., 1990), the structures of quite a few PTTH cDNAs have been described, including Samia cynthia (Ishizaki & Suzuki, 1994), Antheraea pernyi (Sauman & Reppert, 1996), Hyalophora cecropia (Sehnal et al ., 2002), M. sexta (Shionoya et al ., 2003), and several noctuids including Heliothis virescens (Xu & Denlinger, 2003), Helicoverpa zea (Xu et al ., 2003), Helicoverpa armigera (Wei et al ., 2005), and Spodoptera exigua (Xu et al ., 2007). These PTTHs are exclusively from Lepidoptera.…”
Section: Discussionmentioning
confidence: 99%
“…The homology drops dramatically when PTTH from Drosophila is compared with that from C. pipiens , though both are Diptera, but PTTH sequences are still well conserved at the family level. For example, among the four PTTHs known from Saturniidae, the lowest identity of mature PTTH is 71% between S. cynthia and Antheraea pernyi ; among the five PTTHs known from Noctuidae, the lowest identity of mature PTTH is 68%, between H. zea and S. exigua (Xu et al ., 2007). In the four Culicidae compared in the present study the lowest identity of mature PTTH is 84%, between C. pipiens and An.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas (1991) suggested the introduction of phytoecdysteroid (plant chemicals similar to insect hormones) to prevent insect development. Several genes have been isolated from armyworms including chitinase (Bolognesi et al, 2005), pheromone (Xu et al, 2007a) and prothoracicotropic hormone (Xu et al, 2007b). Transgenic corn plants engineered to express the western corn rootworm (Diabrotica virgifera virgifera) double-stranded RNAs show a significant reduction in pest feeding damage in a growth chamber assay (Baum et al, 2007).…”
Section: Transgenic Pest Resistancementioning
confidence: 99%